ESTIMATION OF Na GENE FREQUENCY ON NATIVE CHICKEN POPULATION AND ITS EFFECT ON HATCHABILITY PERFORMANCE - Setianto, J.; Warnoto, W.; Triadi, T. (Diponegoro University, 2009)
The objective of this research was to estimate the Na gene frequency of the native chickenpopulation and its effect on hatchability performance. The research used Native Chickens with Nakedneckphenotype and Normal-feathered Native Chicken, consisted of 16 cocks and 48 hens as the parent.They were put in 4 breeding groups : 1) Breeding group of Legund Cock with Legund Hen (LL); 2)Legund Cock with Normal-feathered Native Hen (LN); 3) Normal-feathered Native Cock with LegundHen (NL); 4) Normal-feathered Native Cock with Normal-feathered Native Hen (NN). Each groupconsisted of 4 replications and each replication consisted of 1 Cock with 3 Hens. CompletelyRandomized Design (CRD) were used to analysis the fertility, hatchability and embryo mortality.Hardy-Weinberg’s Law of Gene equilibrium method was used to find out the spreading estimation of Naand na gene in whole offspring population. Experimental result showed that the breeding groups had noinfluence (P>0.05) on egg fertility, hatchability and embryo mortality. The phenotypes of the offspringof the breeding groups were not deviate from the Mendel’s law. The estimation of the Na gene frequencywas 19.7%.